The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.15265/iy-2015-003
|View full text |Cite
|
Sign up to set email alerts
|

Informatics Systems and Tools to Facilitate Patient-centered Care Coordination

Abstract: SummaryIntroduction: There is a growing international focus on patient-centered care. A model designed to facilitate this type of care in the primary care setting is the patient-centered medical home. This model of care strives to be patient-focused, comprehensive, team-based, coordinated, accessible, and focused on quality and safety of care. Objective: The objective of this paper is to identify the current status and future trends of patient-centered care and the role of informatics systems and tools in faci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 47 publications
0
16
0
Order By: Relevance
“…Even in the Netherlands, where internet usage is extremely high, patients showed a lack of awareness and motivation to hold their own health records, and there were usability problems in the systems for accessing them. 85 There have been similar experiments in Sweden, with mixed success. 23 …”
Section: Causal Link 2:6 -Contextsmentioning
confidence: 95%
See 4 more Smart Citations
“…Even in the Netherlands, where internet usage is extremely high, patients showed a lack of awareness and motivation to hold their own health records, and there were usability problems in the systems for accessing them. 85 There have been similar experiments in Sweden, with mixed success. 23 …”
Section: Causal Link 2:6 -Contextsmentioning
confidence: 95%
“…103 These contradictory findings may be explained by the slow uptake of personal health records, and a lack of studies connecting personal health records to patient outcomes. 85 Another study (reported in Bauer et al…”
Section: Causal Link 6:7 -Contextsmentioning
confidence: 98%
See 3 more Smart Citations